Effectiveness of Ice Pack Application on Level of Pain and Bruise Formation among Patients Receiving Subcutaneous Low Molecular Weight Heparin at Selected Hospitals of City - Girigosavi Rani Kiran; Adhav Prajakta Niranjan, (Research & Review: Management of Emergency and Trauma Nursing (e-ISSN: 2582-0494), 2021)
Background: Bruising is one of the most common adverse events following administration of enoxaparin sodium, which can lead to unpleasant consequences such as reduced access to various sites for injection, reduced satisfaction of patients from treatment and care provided. Cold application is helpful for better management of these side effects which could be easily accessible and economical for the patients. Cold application appears to be cheaper and easily available. Aim: The purpose of this study was to identify the effectiveness of ice pack application on level of pain and bruise formation among patients receiving subcutaneous low molecular weight heparin. Method: Quasi experimental nonequivalent control group posttest only design was adopted. The population comprised of 60 patients receiving subcutaneous low molecular weight heparin from selected hospitals of Pune. Sample of the study were 60 patients receiving subcutaneous low molecular weight heparin patients selected by convenient sampling. The patients in experimental group were provided with ice pack application before receiving subcutaneous low molecular weight heparin to reduce the level of pain and bruise formation. Data was collected by using numerical pain scale, visual analog scale and transparent ruler scale. Result: The study findings showed that average numerical pain score in experimental group was 3.87 and 6.33 in control group. Bruise size was measured in cm. In experimental group Average bruise formation size was 0.0233 after 24 hours of injection, 0.1633 after 48 hours of injection and 0.1766 after 72 hours of injection compared to control group 0.2733 after 24 hours of injection, 0.3933 after 48 hours of injection and 0.4066 after 72 hours of injection. There is significant difference in mean scores of experimental and control group. Conclusion: The findings of the study shows that the ice pack application is effective in reducing the level of pain and bruise formation among patients receiving subcutaneous low molecular weight heparin.